2014
DOI: 10.1051/0004-6361/201322680
|View full text |Cite
|
Sign up to set email alerts
|

The puzzling symbiotic X-ray system 4U1700+24

Abstract: Context. Symbiotic X-ray binaries form a subclass of low-mass X-ray binary systems consisting of a neutron star accreting material from a red giant donor star via stellar wind or Roche lobe overflow. Only a few confirmed members are currently known; 4U 1700+24 is a good candidate as it is a relatively bright X-ray object, possibly associated with the late-type star V934 Her. Aims. We analysed the archive XMM-Newton and Swift/XRT observations of 4U 1700+24 in order to have a uniform high-energy (0.3−10 keV) vie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…The FPM spectra could be equivalently well described using the addition of a black-body component to the cut-off powerlaw in place of the two absorption features. The presence of a similar thermal component would not be unexpected, as it was previously reported for this source by Nucita et al (2014) while analyzing XMM-Newton and SwiftXRT data outside the outbursts. If we compare the results from these authors with those in Table 3, we note that the black-body component required by the NuSTAR data is significantly hotter (1.4 keV vs. the previously reported 0.7-1.0 keV) and would be dominating a large portion of the XRT energy coverage.…”
Section: Igr J17329−2731supporting
confidence: 82%
See 1 more Smart Citation
“…The FPM spectra could be equivalently well described using the addition of a black-body component to the cut-off powerlaw in place of the two absorption features. The presence of a similar thermal component would not be unexpected, as it was previously reported for this source by Nucita et al (2014) while analyzing XMM-Newton and SwiftXRT data outside the outbursts. If we compare the results from these authors with those in Table 3, we note that the black-body component required by the NuSTAR data is significantly hotter (1.4 keV vs. the previously reported 0.7-1.0 keV) and would be dominating a large portion of the XRT energy coverage.…”
Section: Igr J17329−2731supporting
confidence: 82%
“…By using the online tool webpimms 4 and the spectral model measured from the Chandra + NuSTAR data, we converted the above values into a 3 σ upper limit on the source 0.5-10 keV X-ray flux of 8.6×10 −13 erg cm −2 s −1 and 5.6×10 −13 erg cm −2 s −1 , respectively. 4 https://heasarc.gsfc.nasa.gov/cgi-bin/Tools/w3pimms/w3pimms.pl 3 4U 1700+24 4U 1700+24 was discovered in the '70s and it is known since then to be a relatively bright persistent X-ray source (see, e.g., Garcia et al 1983;Nucita et al 2014;Hinkle et al 2019, and references therein). The source is known to host an accreting NS which pulsations have been so far elusive most likely due to the pole-on direction through which the system is being observed.…”
Section: Introductionmentioning
confidence: 99%
“…Again the requirement is that the system is observed nearly pole on with the magnetic and rotation poles aligned. The O VIII line observation was confirmed by Nucita et al (2014). They endorsed both the small size of the X-ray emitting area and the nearly pole on aspect of the NS.…”
Section: A Brief Review Of Hd 154791 = V934 Her = 4u 1700+24mentioning
confidence: 74%
“…They found this is in agreement with the emitting gas being accreted by the NS at the magnetospheric radius. Nucita et al (2014) found that this is ∼1000 km above the NS. Again the requirement is that the system is observed nearly pole on with the magnetic and rotation poles aligned.…”
Section: A Brief Review Of Hd 154791 = V934 Her = 4u 1700+24mentioning
confidence: 89%
“…Nevertheless, in the case of a quarkcluster star, an additional so-called strangeness barrier exists on the quark-cluster surface. Xu (2014) demonstrated that a quark-cluster star may be surrounded by a hot corona or an atmosphere, or even a crust for different accretion rates, which could be helpful to understand the O viii Lyα emission line in 4U 1700+24 (Nucita et al 2014). The mass of the corona or atmosphere or crust is much less than the conventional value ∼10 −5 M of a strange star; hence, the scale is negligible compared with the radius of NSs.…”
Section: Discussionmentioning
confidence: 99%